Direct oral anticoagulants are effective and safe for the treatment of venous thromboembolism associated with gynecological cancers. Issue 2 (29th August 2019) - Shimizu, Aasa; Sawada, Kenjiro; Shiomi, Mayu; Kawano, Mahiru; Matsumoto, Yuri; Takiuchi, Tsuyoshi; Kodama, Michiko; Kobayashi, Eiji; Hashimoto, Kae; Mabuchi, Seiji; Ueda, Yutaka; Tomimatsu, Takuji; et al.
Abstract: Objective: To retrospectively review the efficacy and safety of novel direct oral anticoagulants (DOACs) and compare the results with those of vitamin K antagonists (VKA) when used in clinical practice to treat venous thromboembolism (VTE) because there is insufficient evidence regarding its use in patients with gynecological cancers. Methods: A study was conducted of patients diagnosed with gynecological cancers at Osaka University Hospital between January 2010 and December 2017. The medical records of those who suffered from deep venous thrombosis (DVT) and/or pulmonary embolism (PE) were retrospectively reviewed. Results: Among the 1698 cases of gynecological cancers, 107 (6.3%) cases were diagnosed as having VTE. A total of 34 (31.8%) patients presented DVT plus PE and 73 (68.2%) patients had DVT alone. Fifty‐four cases were treated with DOACs and 53 with VKA. Although 3 of the 53 patients (5.7%) in the VKA group developed recurrent VTE, only 1 (1.9%) patient in the DOAC group showed clinically relevant bleeding from a tumor penetrating the rectum. DOACs were non‐inferior to VKA with respect to the composite outcome, including recurrent venous thrombosis and relevant bleeding (hazard ratio 0.31, 95% confidence interval 0.03–3.12, P =0.363). Conclusion: DOACs can be effectively and safely used in VTE patients with gynecological cancers. Abstract : Direct oral anticoagulants can be effectively and safely used for the treatment of venous thromboembolism in patients with gynecological cancers.